ORGANIZATION AND MANAGEMENT OF PRESCHOOL EDUCATION ORGANIZATION BASED ON INFORMATION COMMUNICATION AND DIGITAL TECHNOLOGIES (World Bulletin of Social Sciences, 2023)
Today, it is impossible to imagine the development of any field without information and communication technologies and innovations. One of the most urgent tasks is to use modern information technologies and introduce innovations in the field, especially in the education and upbringing of the young generation. This article talks about the organization and management of Preschool Education Organization based on information communication and digital technologies.
Keywords: education; training; game; interactive technology